2015
DOI: 10.1590/1678-4499.0264
|View full text |Cite
|
Sign up to set email alerts
|

Germinação de pólen e aplicação de ácido bórico em botões florais de nespereiras

Abstract: of boric acid on field raised the pollen grain germination to 57.68%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 19 publications
1
7
0
1
Order By: Relevance
“…Five anthers were then separated at random, and each set of anthers stored in uncapped Eppendorf tubes at a controlled temperature (27 °C) for 24 h in the absence of light, for dehiscence to take place with the release of pollen grains (NOGUEIRA et al, 2015). After 24 hours, a solution of 1,000 µl of lactic acid was added to the tube.…”
Section: Quantification Of Pollen Grains Per Anther and Per Flowermentioning
confidence: 99%
“…Five anthers were then separated at random, and each set of anthers stored in uncapped Eppendorf tubes at a controlled temperature (27 °C) for 24 h in the absence of light, for dehiscence to take place with the release of pollen grains (NOGUEIRA et al, 2015). After 24 hours, a solution of 1,000 µl of lactic acid was added to the tube.…”
Section: Quantification Of Pollen Grains Per Anther and Per Flowermentioning
confidence: 99%
“…Similar results were observed when using calcium nitrate in the in vitro germination of pollen grains of peach and pear trees (Chagas et al 2009). Similarly, according to Nogueira et al (2014), the culture medium absent of calcium nitrate promoted more germination of loquat pollen grains.…”
Section: Resultsmentioning
confidence: 90%
“…This was most likely related to a gradual increase in the solute concentration of the medium that disrupted the integrity of the pollen grain cell structure (Dantas et al 2005). The application of boric acid in the field raised the pollen grain germination of loquat (Nogueira et al 2014), which proves the need for boric acid in pollen grain germination.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, in analyzing Eriobotrya japonica, Nogueira et al (2015) found a linear increase in the pollen germination percentage as the agar concentration increased. The same behavior was observed in relation to the addition of sucrose to the culture medium.…”
Section: Discussionmentioning
confidence: 96%